The principle of distinction and modern armed conflicts: a critical analysis of the protection regime based on the distinction between civilians and combatants under international humanitarian law - Chigowe, Lloyd Tonderai (Rhodes University, Faculty of Law, Law, 2017)
This thesis interrogates the applicability of the principle of distinction in modern armed conflicts. The distinction between combatants and civilians and between civilian objects and military objectives has become blurred as a result of the changes that have taken place in modern armed conflicts. While the principle of distinction was tailor made to regulate traditional, conventional armed conflicts, an evolution in the nature, means and methods of warfare has made the application of the principle of distinction challenging. One of the challenges that arise as a result of the changes that have taken place in modern armed conflicts include the difficulty of distinguishing civilians and civilian objects, which are entitled to protection under international humanitarian law from combatants and military objectives which are legitimate targets. This has compromised the protection that the law seeks to offer during armed conflicts since civilians and civilian objects have become constant targets. Another challenge is that the involvement of civilian persons in armed conflicts has made it difficult to determine the responsibility of these individuals as well as the states that hire them for violations of international law during armed conflicts. Furthermore, the emergence of new methods of warfare has resulted in many objects and facilities that are traditionally regarded as civilian objects becoming military objectives, thus losing their protection under international humanitarian law. This thesis will use the examples of the involvement of private military and security companies in armed conflicts as well as the emergence of drone and cyber warfare to illustrate these challenges. The study will examine the application of the principle of distinction to the growing practice of outsourcing of military services to Private Military and Security Companies. Firstly, the study will examine the status of PMSC personnel under the principle of distinction, that is whether they qualify as combatants or civilians. The study will then examine the consequences of PMSC personnel's participation in armed conflicts. Importantly, the study will explore responsibilities of states that hire private military and security personnel, PMSC companies as well as superiors in charge of PMSC personnel for any violation of international law committed by contractors during armed conflicts. The study will also examine the application of the principle of distinction to drone and cyber warfare. The study will examine the status of drone and cyber operators under the principle of distinction as well as the applicability of the principle of distinction between civilian objects and military objectives in drone and cyber warfare. The study will discuss some of the problems that arise as result of the introduction of these new methods of warfare, which makes the application of the principle of distinction to modern armed conflicts challenging. The thesis concludes by arguing that while the principle of distinction remains an indispensable concept of international humanitarian law, it needs to be adapted for it to be applicable to modern armed conflicts. Therefore, suggestions shall be made on how the principle can be adapted to ensure that it remains relevant to modern armed conflicts.
Keywords: Humanitarian law; Military art and science -- Law and legislation; Combatants and noncombatants (International law); Military law; National security -- Law and legislation; Private military companies (International law); Human rights -- International cooperation; Soft law